Dynamic Parameters of the Space Environment. (Space Etheras Dynamics) (Global Journal of Science Frontier Research, 2014)
This paper presents a new dynamic approach to studies of the space environment. The author has explored a mechanism to produce vortex flows of muons and π -mesons in the space, their stability at superlight velocities. It submits numerical values of parameters for the ether's dynamic space environment and presents more details for the principle of mass equivalence.
Keywords: neo-ether; ether’s dynamics; dipole; medium density; pressure; temperature; dynamic viscosity; kinematic viscosity; muon; π -meson; reynolds number